2014
DOI: 10.1007/s00421-014-2820-2
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular structure, function, and focal fibrosis in anabolic steroid users: a CMR study

Abstract: AS use was associated with significant LV hypertrophy, albeit in-line with greater fat-free mass, reduced LV strain, diastolic function, and reduced RV ejection fraction in male bodybuilders. There was, however, no evidence of focal fibrosis in any AS user.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
5
15
0
4
Order By: Relevance
“…Cardiac fibrosis was more common and outstanding when compared to hypertrophy in cardiac muscles. These lesions and others such as disorganized muscle fibers, misshapen nuclei and increasing apoptosis have also been described in previous studies (Belhani et al 2009, Papamitsou et al 2011, Angell et al 2012, Angell et al 2014.…”
Section: Discussionsupporting
confidence: 78%
“…Cardiac fibrosis was more common and outstanding when compared to hypertrophy in cardiac muscles. These lesions and others such as disorganized muscle fibers, misshapen nuclei and increasing apoptosis have also been described in previous studies (Belhani et al 2009, Papamitsou et al 2011, Angell et al 2012, Angell et al 2014.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, some recent innovative diagnostic techniques, such as pulsed-wave tissue Doppler imaging and ultrasonic-integrated backscatter cyclic variation analysis [19] and cardiac magnetic resonance (CMR) [20], documented regional systolic and diastolic dysfunction in AAS users with respect to AAS non-users or control cases. Angell and colleagues [21] could detect pathological alterations of ventricular structure and dysfunction in the hearts of AAS users in CMR analyses. However, focal cardiac fibrosis, which is almost found histopathologically in AAS users, could not be detected by the use of CMR.…”
Section: Discussionmentioning
confidence: 98%
“…This is in stark contrast to the work of Abergel et al, 4 who found 8.7% of elite cyclists presented a MWT exceeding 13 mm. It is difficult to speculate as to the reason for this disparity, however, the authors themselves report the potential confounding impact of performance‐enhancing drugs used by cyclists during the 1990s and early 2000s, many of which are known to elicit concentric LVH 35 . Better endocardial border differentiation from a combination of improvement in echocardiography technology and experience in defining true endocardium from LV trabeculation may potentially have also contributed to previously erroneous measurements.…”
Section: Discussionmentioning
confidence: 99%